Предмет: Алгебра,
автор: АНЯ505404
упростите выражение: 1) (a+b)^2 -(a-b)^2 2) (m+4)^2 -4(m+1)^2
Ответы
Автор ответа:
0
1) = а^2+2ab+b^2-(a^2-2ab+b^2)=a^2+2ab+b^2-a^2+2ab-b^2=4ab;
2) = (m^2+8m+16)-4(m^2-2m+1)= m^2+8m+16-4m^2+8m-4= -3m^2+16m+12;
2) = (m^2+8m+16)-4(m^2-2m+1)= m^2+8m+16-4m^2+8m-4= -3m^2+16m+12;
Автор ответа:
0
Спасибо огромное ^3^
Похожие вопросы
Предмет: Українська мова,
автор: Аноним
Предмет: Биология,
автор: veronikamihajluk0105
Предмет: Русский язык,
автор: dariaparomova
Предмет: Геометрия,
автор: elizavetamarga
Предмет: Обществознание,
автор: alinkakislyak